YSZ (Yttria Stabilized Zirconia)-based mixed potential type SO2 sensor adopting novel sensitive electrode material as well as preparation method and application of YSZ-based mixed potential type SO2 sensor
By using the structural design of the new sensitive electrode material MnxZrxNbyOz and YSZ-based hybrid potential type SO2 sensor, the problem of long response and recovery time for detecting high-concentration SO2 gases in the prior art is solved, and fast response and accurate detection in high-temperature environments are achieved, with a wide detection range and good stability.
Patent Information
- Application Number
- CN202411648038.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
AI Technical Summary
The existing SO2 sensors have a long response and recovery time when detecting high-concentration SO2 gases, making it difficult to achieve accurate real-time detection, and the detection range is generally low.
The new sensitive electrode material MnxZrxNbyOz is prepared by gel sol method, combined with the structural design of the YSZ-based hybrid potential type SO2 sensor, which improves the response and sensitivity of the sensor.
It realizes rapid response and accurate detection of high-concentration SO2 gas in high temperature environments, with a wide detection range and good repeatability and stability.
Smart Images

Figure CN119555769A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas sensors, and in particular to a YSZ-based hybrid potential type SO 2 Sensor and its preparation method and application. Background Art
[0002] In recent years, with the rapid development of my country's economy, the degree of industrialization has been further deepened. However, the energy economic structure dominated by fossil fuels has also brought serious air pollution problems. As people's awareness of environmental protection and air pollution continues to increase, my country has formulated strict exhaust emission standards for mobile pollution sources such as cars and fixed pollution sources such as factories. In order to smoothly implement the emission standards and for the targeted treatment of exhaust gas, it is urgent to develop sensors that can detect the concentration of exhaust gas in real time.
[0003] SO 2 It is one of the main air pollutants, mainly from industrial production, thermal power generation, fuel vehicle emissions and other processes. According to statistics, SO 2 The emission volume was 2.435 million tons, of which SO 2 The emission volume was 1.835 million tons, accounting for SO 2 75.3% of total emissions. SO 2 Sulfate mist and sulfate aerosol will form in the air, which will also oxidize in the air to form acid rain, leading to soil acidification and damaging ecosystems and building facilities. 2 It can also harm human health. When inhaling excessively high concentrations of SO 2 The gas can cause nausea, vomiting, respiratory diseases and other serious side effects. 2 When the gas enters the human blood circulation, it will affect the activity of human enzymes, leading to decreased immune function and causing cardiovascular diseases. 2 The severe environmental challenges and health threats caused by the 2 Gas sensors to detect high concentration range SO in real time 2 gas.
[0004] Thanks to SO 2 The nature of SO is complex and it is difficult to detect it stably and reliably in real time. Most of the sensors currently developed focus on the detection of 10ppm and ppb levels. In fact, SO 2 The concentration of the gas can be as high as several hundred ppm, but it can detect high concentration SO 2 There are only a handful of sensors that can detect SO. Usually, an auxiliary electrode is required to use metal sulfide or sulfate as a sensing electrode. However, this type of sensor has a long response and recovery time, making it difficult to accurately identify SO in a timely manner.2 Gas concentration, which limits its application to a certain extent.
[0005] Compared with the above sensors, solid electrolyte sensors, especially hybrid potential sensors based on yttrium-stabilized zirconia, have the characteristics of low manufacturing cost, small size, miniaturized device structure, good chemical stability, high sensitivity and response signal, as well as good response recovery characteristics and repeatability. They can meet the requirements of real-time monitoring in the harsh environment of high air velocity, high temperature and high humidity of exhaust gas. According to the mechanism of hybrid potential sensors, the sensor is sensitive to SO 2 The electrochemical response of the gas is at the sensitive electrode / SO 2 The three-phase interface (TPB) of gas / YSZ solid electrolyte is generated, so the electrochemical catalytic activity of the sensitive electrode material plays an important role in the sensitive response performance of the gas. The gas sensor is based on the interaction between the sensor material and the target gas. Therefore, it is necessary to find and develop a method for SO 2 Sensitive electrode materials with gas-specific adsorption and high electrochemical catalytic activity are very important. Summary of the invention
[0006] The purpose of the present invention is to provide a YSZ-based hybrid potential SO with a new sensitive electrode material, which can meet the high temperature test environment, has good sensitivity, response / recovery characteristics, repeatability, stability and a wide detection range. 2 Sensor and its preparation method and application.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention is to provide a YSZ-based hybrid potential type SO 2 The sensor comprises: a first Al 2 O 3 The porous layer, the heating electrode layer, the first YSZ electrolyte layer, the reference electrode, the second YSZ electrolyte layer, the sensitive electrode and the second Al 2 O 3 Porous layer; wherein the sensitive electrode is made of Mn x Zr x Nb y O z Prepared.
[0009] Preferably, Mn x Zr x Nb y O z In, x:y:z=1:2:8.
[0010] The second aspect of the present invention is to provide a YSZ-based hybrid potential type SO 2 The method for preparing a sensor comprises the following steps:
[0011] S1, tape casting preparation of the first Al 2 O 3 Porous layer, second Al 2 O 3 A porous layer, a first YSZ electrolyte layer, and a second YSZ electrolyte layer;
[0012] S2, by screen printing on the first Al 2 O 3 A heating circuit is brushed on the top of the porous layer, and a Pt resistance circuit is brushed on the bottom of the first YSZ electrolyte layer, and the Pt resistance circuit is connected to the heating circuit; a reference electrode Pt and a Pt wire connected to the reference electrode are brushed on one side of the top of the first YSZ electrolyte layer; another Pt wire and a Pt pin for connecting the sensitive electrode are brushed on the top of the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin;
[0013] S3, the first Al with heating circuit 2 O 3 porous layer, a first YSZ electrolyte layer with a reference electrode, a second YSZ electrolyte layer with a Pt pin, and a second Al 2 O 3 After the porous layers are stacked in sequence, they are subjected to hot pressing and sintering treatment to obtain a sheet-type sensor without brushing sensitive electrodes;
[0014] S4, brush the sensitive electrode slurry to the other side of the top of the second YSZ electrolyte layer through screen printing, and connect another Pt wire to the sensitive electrode; sinter the sheet-type sensor brushed with the sensitive electrode slurry to obtain the YSZ-based hybrid potential type SO 2 sensor.
[0015] Preferably, in step S4, the step of preparing the sensitive electrode slurry comprises: weighing an organic binder, Mn x Zr x Nb y O z The powder and fish oil are placed in a mortar and ground for 1-2 hours to obtain a sensitive electrode slurry.
[0016] More preferably, the organic binder and Mn x Zr x Nb y O z The mass ratio of the powder is (1:1)-(4:6), and the mass of the fish oil is 0.5%-1.5% of the mass of the sensitive electrode slurry.
[0017] More preferably, the preparation step of the organic binder comprises: weighing pineneol into a beaker, adding 2.5-3.5wt% fish oil, stirring at 90°C, and adding 0.8-0.9wt% ethyl cellulose in batches, with an interval of 0.5-2h between each batch, for a total of five batches.
[0018] More preferably, Mn x Zr x Nb y O z The preparation steps of the powder include: weighing manganese oxalate, zirconium nitrate and niobium oxalate according to the element ratio and dissolving them in deionized water; stirring at a constant temperature of 70-75°C; adding citric acid in an amount of 1-4 times the amount of metal ions, EDTA in an amount of 1-3 times the amount of metal ions and ammonia water; adjusting the pH of the solution to 7-8.5; continuing to stir to obtain a gel; and sequentially drying and calcining the gel to obtain Mn x Zr x Nb y O z powder.
[0019] More preferably, the drying treatment is carried out at a temperature of 200-260° C. for 4-12 h; and the calcination treatment is carried out at a temperature of 800-850° C. for 3-6 h.
[0020] Preferably, in step S4, the sintering treatment includes: heating to 1000°C at a rate of 1-4°C / min, sintering for 2h, and then cooling at a rate of 3-6°C / min.
[0021] The third aspect of the present invention is to provide a YSZ-based hybrid potential type SO 2 Sensor or YSZ-based hybrid potential-type SO prepared by the above preparation method 2 Sensors detect SO in-situ in industrial exhaust gas 2 Application, the YSZ-based hybrid potential type SO 2 The temperature test range of the sensor is 340-400℃, SO 2 The test concentration is 0-500ppm and the oxygen test range is 2-21%.
[0022] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0023] (1) The present invention prepares a SO 2 A new sensitive electrode material Mn with high catalytic activity for gases x Zr x Nb y O z , is a mixed potential type SO 2The sensitive electrode of the sensor provides a new electrode material with a simple preparation method, controllable conditions, and non-toxic raw materials, which can be conducive to industrial mass production.
[0024] (2) The sensitive electrode material Mn of the present invention x Zr x Nb y O z Using Mn ions to react with SO 2 Good capture and adsorption capacity, multivalent variability of Nb ions, and SO 2 The specific catalytic ability of the gas and the conduction of oxygen ions by Zr ions and the adsorption of SO 2 The ability to improve Mn x Zr x Nb y O z About SO 2 The adsorption and electrochemical catalytic activity of gases, and the conduction of Zr ions to oxygen ions enhance the SO 2 Converted into SO at the three-phase interface 3 The electrochemical catalytic process improves the sensor's sensitivity to SO 2 Response.
[0025] (3) The sensitive electrode material Mn of the present invention x Zr x Nb y O z After sintering, the surface particle size is 40-120nm. Small-sized particles are conducive to the increase of three-phase interface and promote SO 2 The electrochemical catalytic reaction improves the sensor's sensitivity to SO 2 In addition, the small-sized particles are connected to form a network structure, which promotes the conduction of oxygen ions. In addition, the surface of the sensitive electrode material has good pore gaps, which promotes SO 2 The gas diffuses to the three-phase interface, reducing SO 2 gas phase reaction.
[0026] (4) The present invention adopts the tape casting technology to prepare the YSZ electrolyte layer, and adopts Mn x Zr x Nb y O z The sensor is prepared as a sensitive electrode, so that the sensor can have good chemical stability even at high temperatures and meet the requirements of harsh testing conditions.
[0027] (5) YSZ-based hybrid potential SO of the present invention 2 The sensor adopts a sheet-type structure, which is low in cost, small in size and can be produced in large quantities.
[0028] (6) YSZ-based hybrid potential type SO of the present invention 2 The sensor can detect a wide range of SO concentrations 2 Gas, which solves the problem that the existing sensor test concentration is generally low.
[0029] (7) YSZ-based hybrid potential SO of the present invention 2 The sensor can be used directly after packaging, which greatly shortens the time it takes to put the sensor into commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a YSZ-based hybrid potential type SO in one embodiment of the present invention. 2 Schematic diagram of the basic structure of the sensor;
[0031] Figure 2 YSZ-based hybrid potential SO 2 Schematic diagram of the sensor packaging process;
[0032] Figure 3 MnZrNb calcined at 800℃ 2 O 8 and XRD patterns of the sensitive electrode sintered at 1000 °C;
[0033] Figure 4 MnZrNb 2 O 8 Schematic diagram of the microstructure after calcination at 800℃;
[0034] Figure 5 Schematic diagram of the microscopic morphology of the sensitive electrode;
[0035] Figure 6 At a working temperature of 340-400°C, the YSZ-based hybrid potential type SO 2 Comparison of sensor response size at 0-500ppm;
[0036] Figure 7 At a working temperature of 340-400°C, the YSZ-based hybrid potential type SO 2 Sensor to SO 2 Sensitivity curve of
[0037] Figure 8 At a working temperature of 400°C, the YSZ-based hybrid potential type SO 2 Sensor for 100ppm SO 2 and 500ppm SO 2 Response recovery time curve;
[0038] Fig. 9At a working temperature of 400°C, the YSZ-based hybrid potential type SO 2 Sensor stability test results;
[0039] Fig.10 At a working temperature of 400°C, the YSZ-based hybrid potential type SO 2 Sensor for 100ppm SO 2 Response size at different oxygen concentrations. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0042] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0043] Example
[0044] like Figure 1 As shown, this embodiment provides a YSZ-based hybrid potential type SO using a new sensitive electrode material 2 The sensor and the preparation method thereof, the steps comprising:
[0045] S1, tape casting preparation of the first Al 2 O 3 Porous layer, second Al 2 O 3 A porous layer, a first YSZ electrolyte layer, and a second YSZ electrolyte layer;
[0046] S2, by screen printing on the first Al 2 O 3 A heating circuit is brushed on the top of the porous layer, and a Pt resistance circuit is brushed on the bottom of the first YSZ electrolyte layer, and the Pt resistance circuit is connected to the heating circuit; a reference electrode Pt and a Pt wire connected to the reference electrode are brushed on one side of the top of the first YSZ electrolyte layer; another Pt wire and a Pt pin for connecting the sensitive electrode are brushed on the top of the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin;
[0047] S3, the first Al with heating circuit 2 O 3porous layer, a first YSZ electrolyte layer with a reference electrode, a second YSZ electrolyte layer with a Pt pin, and a second Al 2 O 3 After the porous layers are stacked in sequence, they are subjected to hot pressing and sintering treatment to obtain a sheet-type sensor without brushing sensitive electrodes;
[0048] S4, brush the sensitive electrode slurry to the other side of the top of the second YSZ electrolyte layer through screen printing, and connect the sensitive electrode with another Pt wire; sinter the sheet-type sensor brushed with the sensitive electrode slurry at 1000℃ for 2h, with a sintering heating rate of 2℃ / min and a cooling rate of 5℃ / min. After sintering, the YSZ-based hybrid potential type SO 2 sensor;
[0049] The preparation steps of the sensitive electrode slurry include: weighing 0.4g organic binder, 0.6g MnZrNb 2 O 8 The powder and 0.01 g of fish oil were placed in a mortar and ground for 2 h to obtain a sensitive electrode slurry;
[0050] The preparation steps of the organic binder include: weighing pinene alcohol and placing it in a beaker, adding 3.5wt% fish oil, stirring at a constant temperature of 90°C, and adding 0.8wt% ethyl cellulose in batches, with an interval of 1h between each batch, for a total of five batches;
[0051] MnZr 2 O 8 The preparation steps of the powder include: weighing 1mmol of manganese oxalate, 1mmol of zirconium nitrate and 2mmol of niobium oxalate according to the element ratio and dissolving them in deionized water, stirring at a constant temperature of 75°C, adding 6mmol of citric acid and 4mmol of EDTA, adding ammonia water drop by drop, adjusting the pH of the solution to 7, continuing to stir to obtain a gel, drying the gel at 240°C for 4h to obtain a dry gel, and calcining the dry gel at 800°C for 2h to obtain MnZrNb 2 O 8 powder.
[0052] Detection Example
[0053] like Figure 2 As shown, the YSZ-based hybrid potential type SO prepared by the preparation method described in the embodiment 2 The sensor was inserted into a cylindrical ceramic block to fix the sensor, and then the sensor was placed in a metal shell. An appropriate amount of talcum powder was taken as a sealing powder and filled into the metal shell. The sensor was then placed on a piezoelectric feeder mold and fixed. The sealing powder was compacted into the metal shell by pressure. The positive side wiring port of the sensor was connected to an electrochemical workstation. A dynamic test was performed to test the sensor at a flow rate of 4000 and different oxygen concentrations in the range of 0-500ppm SO 2The change of voltage in the atmosphere, the result is as follows Figure 6-10 As shown;
[0054] At the same operating temperature, the sensor response value increases with SO 2 The concentration of SO increases inversely. 2 Gas, within a certain temperature range, as the operating temperature decreases, the response value increases, 350℃, 500ppmSO 2 In the gas, the response potential difference reaches -51.96mv; it can be seen that the sensor of the present invention has a wider temperature range ( Figure 6 );
[0055] At different working temperatures, the sensor responds to SO 2 The response of the gas is negative linear, which conforms to the principle of mixed potential. The sensor of the present invention has good sensitivity, reaching the maximum sensitivity at 350°C, with a sensitivity of -24.73mv / decade ( Figure 7 );
[0056] At 400℃, the sensor is resistant to 100ppm SO 2 The response and recovery time of the gas were 32s and 112s respectively; for 500ppm SO 2 The response and recovery times of the gas were 25s and 74s, respectively. This may be because the higher the gas concentration, the more SO can reach the three-phase interface. 2 More gas, faster reaction to reach equilibrium ( Figure 8 );
[0057] At 400℃ working temperature, the sensor can detect low concentration of 100ppm SO 2 and high concentrations of 500ppm SO 2 In gas, it has good repeatability and stability ( Fig. 9 );
[0058] At 400℃, the sensor response is linearly related to the logarithm of oxygen concentration, which is consistent with the hybrid potential principle ( Fig.10 ).
[0059] MnZrNb 2 O 8 The powder and sensitive electrode were tested for morphology. Figure 3-5 As shown; after calcination at 800℃, the monoclinic MnZrNb 2 O 8 Powder, corresponding to standard card JCPDS#48-0331; MnZrNb 2 O 8After the sensor with sensitive electrode was sintered at 1000℃, no impurities appeared on the surface of the sensitive electrode, and only MnZrNb 2 O 8 and YSZ phase ( Figure 3 ); MnZrNb 2 O 8 The powder is composed of multiple particles in the form of flakes or blocks, and the particle size is approximately 20-100nm ( Figure 4 ); The sensitive electrode has a certain network structure and pores, which is conducive to the transmission of ions and gases. At the same time, the thickness of the sensitive electrode layer is about 17.25μm, and the particles of the sensitive electrode are small, which is conducive to the construction of more three-phase interfaces ( Figure 5 ).
[0060] In summary, the present invention uses YSZ as the ion conductive layer, Mn x Zr x Nb y O z Composite oxides as sensitive electrodes to construct a new hybrid potential SO 2 Sensors that detect high concentrations of SO 2 Gas, with high response and sensitivity, short response / recovery time and good repeatability.
[0061] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A YSZ-based hybrid potential SO2 sensor using a new sensitive electrode material, characterized in that: include: The first Al2O3 porous layer, the heating electrode layer, the first YSZ electrolyte layer, the reference electrode, the second YSZ electrolyte layer, the sensitive electrode and the second Al2O3 porous layer are sequentially arranged; wherein the sensitive electrode is made of Mn x Zr x Nb y O z Prepared.
2. The YSZ-based hybrid potential type SO2 sensor according to claim 1, characterized in that: Mn x Zr x Nb y O z where x:y:z = 1:2:
8.
3. A method for preparing a YSZ-based hybrid potential-type SO2 sensor as claimed in any one of claims 1 to 2, characterized in that the steps include: S1, tape casting to prepare a first Al2O3 porous layer, a second Al2O3 porous layer, a first YSZ electrolyte layer and a second YSZ electrolyte layer; S2. Brush a heating circuit on the top of the first Al2O3 porous layer by screen printing, and brush a Pt resistance circuit on the bottom of the first YSZ electrolyte layer, and the Pt resistance circuit is connected to the heating circuit; brush a reference electrode and a Pt wire connected to the reference electrode on one side of the top of the first YSZ electrolyte layer; brush another Pt wire and a Pt pin for connecting the sensitive electrode on the top of the second YSZ electrolyte layer, and both Pt wires are connected to the Pt pin; S3, stacking the first Al2O3 porous layer with a heating circuit, the first YSZ electrolyte layer with a reference electrode, the second YSZ electrolyte layer with a Pt pin, and the second Al2O3 porous layer in sequence, and performing hot pressing sintering treatment to obtain a sheet-type sensor without brushing sensitive electrodes; S4. The sensitive electrode slurry is brushed to the other side of the top of the second YSZ electrolyte layer by screen printing, and another Pt wire is connected to the sensitive electrode; the sheet-type sensor brushed with the sensitive electrode slurry is sintered to obtain a YSZ-based hybrid potential type SO2 sensor.
4. The preparation method according to claim 3, characterized in that: In step S4, the preparation steps of the sensitive electrode slurry include: weighing the organic binder, Mn x Zr x Nb y O z The powder and fish oil are placed in a mortar and ground for 1-2 hours to obtain a sensitive electrode slurry.
5. The preparation method according to claim 4, characterized in that: Organic binder and Mn x Zr x Nb y O z The mass ratio of the powder is (1:1)-(4:6); the mass of the fish oil is 0.5%-1.5% of the mass of the sensitive electrode slurry.
6. The preparation method according to claim 4, characterized in that: The preparation steps of the organic binder include: weighing pinene alcohol and placing it in a beaker, adding 2.5-3.5wt% fish oil, stirring at 90°C, and adding 0.8-0.9wt% ethyl cellulose in batches, with an interval of 0.5-2h between each batch, for a total of five batches.
7. The preparation method according to claim 4, characterized in that: Mn x Zr x Nb y O z The preparation steps of the powder include: weighing manganese oxalate, zirconium nitrate and niobium oxalate according to the element ratio and dissolving them in deionized water; stirring at a constant temperature of 70-75°C; adding citric acid in an amount of 1-4 times the amount of metal ions, EDTA in an amount of 1-3 times the amount of metal ions and ammonia water; adjusting the pH of the solution to 7-8.5; continuing to stir to obtain a gel; and drying and calcining the gel in turn to obtain Mn x Zr x Nb y O z powder.
8. The preparation method according to claim 7, characterized in that: The temperature of the drying treatment is 200-260°C, and the time is 4-12 hours; the temperature of the calcination treatment is 800-850°C, and the time is 3-6 hours.
9. The preparation method according to claim 3, characterized in that: In step S4, the sintering treatment includes: heating to 1000°C at a rate of 1-4°C / min, sintering for 2h, and then cooling at a rate of 3-6°C / min.
10. An application of the YSZ-based hybrid potential-type SO2 sensor as claimed in any one of claims 1 to 2 or the YSZ-based hybrid potential-type SO2 sensor prepared by the preparation method as claimed in any one of claims 3 to 9 in the in-situ detection of SO2 in industrial tail gas, characterized in that: The temperature test range of the YSZ-based hybrid potential SO2 sensor is 340-400°C, the SO2 test concentration is 0-500ppm, and the oxygen test range is 2-21%.